Enhanced radiation hardness and faster front ends for the beetle readout chip - van Bakel, N; van den Brand, J; Verkooijen, H; Bauer, C; Baumeister, D; Hofmann, N; Knopfle, K; Lochner, S; Schmelling, M; Sexauer, E; Feuerstack-Raible, M; Trunk, U; et al. (2001)
This paper summarizes the recent progress in the development of the 128 channel pipelined readout chip Beetle, which is intended for the silicon vertex detector, the inner tracker, the pile-up veto trigger and the RICH detectors(1) of LHCb.Deficiencies found in the front end of the Beetle Version 1.0 and 1.1 chips resulted in the submissions of BeetleFE 1.1 and BeetleFE 1.2, while BeetleSR 1.0 implements test circuits to provide future Beetle chips with logic circuits hardened against single event upset (SEU).Section I. motivates the development of new front ends for the Beetle chip, and section II. summarizes their concepts and construction. Section III. reports preliminary results from the BeetleFE 1.1 and BeetleFE 1.2 chips, while section IV. describes the BeetleSR 1.0 chip. An outlook on future test and development of the Beetle chip is given in section V.